A seamless weather–climate multi‐model intercomparison on the representation of a high impact weather event in the western Mediterranean: HyMeX IOP12. (2nd February 2016) - Khodayar, S.; Fosser, G.; Berthou, S.; Davolio, S.; Drobinski, P.; Ducrocq, V.; Ferretti, R.; Nuret, M.; Pichelli, E.; Richard, E.; Bock, O.
Abstract : High Impact Weather (HIW), particularly Heavy Precipitation Events (HPE), are common phenomena affecting the western Mediterranean (WMED) especially in the autumn period. Understanding and evaluating the capability to adequately represent such events in model simulations is one of the main goals of the Hydrological cycle in the Mediterranean Experiment (HyMeX) and the main motivation of this investigation. In order to gain a better knowledge of the model representation of HPE and related processes we perform a seamless multi‐model intercomparison at the event scale. Limited‐area model runs (grid spacing from 2 to 20 km) at weather and climate time‐scales are considered, four with parametrized and five with explicit convection. The performance of the nine models is compared by analysing precipitation, as well as convection‐relevant parameters. An Intensive Observation Period (IOP12) from the HyMeX‐SOP1 (Special Observation Period) is used to illustrate the results. During IOP12, HPE affected the northwestern Mediterranean region, from Spain to Italy, as a consequence of Mesoscale Convective Systems (MCSs) which initiated and intensified in the area of investigation. Results show that: (i) the timing of the maximum precipitation seems to be linked to the representation of large‐scale conditions rather than differences among models; (ii) Convection Permitting Models (CPMs) exhibit differences among each other, but better represent the short‐intense convective events. All four convection‐parametrized models produce a large number of weak and long‐lasting events. Regional Climate Models (RCMs) capture the occurrence of the event but produce notably lower precipitation amounts and hourly intensities than CPMs and Numerical Weather Prediction (NWP) models with parametrized convection; (iii) these differences do not seem to come from mean moisture or Convective Available Potential Energy (CAPE) which are in the same range for all models, but rather from differences in the variability and vertical distribution of moisture and the triggering of deep convection.